HUBUNGAN ANTARA TINGKAT KONSERVATISME PIHAK PENGAKUSISI DAN TINGKAT RETURN KEGIATAN MERGER-AKUISISI DARI PERSPEKTIF PIHAK PENGAKUISISI - Leona Ami; Yie Ke Feliana (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2017)
Abstract – This research investigate if timely loss recognitionis associated with return of merger - acquisition. In order to measure conservatism, we used Basu (1997) and Francis and Martin (2010) in Demsetz and Lehn (1985) to measure return. Model I with AcqCAR +/- 30 days and Model II with AcqCAR +/- 365 days shows there is no significant relation between conservatism and return from merger and acquisition decision. In addition, we find that Basu (1997) is not significant for sample in Indonesia .Paired sample t-test shows there is no significant changes in return related merger and acquisition decision.